Unveiling Mathematics Concepts on Panggung Krapyak and Rotiban Activities: An Ethnomathematics Study in Yogyakarta - Ashabulabib, Adib; Arfinanti, Nurul (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2024)
The utilization of cultural context in mathematics learning can be an alternative of effective learning approach to bridge students to master the abstract dimension of mathematics through the real context in students' lives. However, cultural integration in mathematics learning must begin with the identification of mathematical concepts contained in cultural objects that are relevant to school mathematics. This study aims to identify mathematical concepts contained in the Panggung Krapyak and Rotiban activities at one of the Islamic boarding schools in Yogyakarta, Indonesia. This study is an exploratory study with a qualitative approach. Data were collected through observations of the Panggung Krapyak and Rotiban activities, in-depth interviews with figures, documentation, and literature reviews. The results of the study indicate that Panggung Krapyak displays various mathematical concepts such as reflection, similarity, and congruence in the shape of the building. In addition, the Rotiban activity contains the concept of multiples of numbers in its schedule and cyclic permutation in the cycle pattern of participants sitting. These findings indicate that the existence of mathematical concepts contained in local culture is in line with school mathematics so it can be integrated into mathematics learning to be more contextual and easier for students understanding.